Correction: Substituent interference on supramolecular assembly in urea gelators: synthesis, structure prediction and NMR. Issue 24 (2nd June 2016) - Piana, Francesca; Case, David H.; Ramalhete, Susana M.; Pileio, Giuseppe; Facciotti, Marco; Day, Graeme M.; Khimyak, Yaroslav Z.; Angulo, Jesús; Brown, Richard C. D.; Gale, Philip A.
Abstract : Correction for 'Substituent interference on supramolecular assembly in urea gelators: synthesis, structure prediction and NMR' by Francesca Piana et al., Soft Matter, 2016, 12, 4034–4043.